The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12966-022-01297-x
|View full text |Cite
|
Sign up to set email alerts
|

Leading the way together: a cluster randomised controlled trial of the 5R Shared Leadership Program in older adult walking groups

Abstract: Background With a rapidly ageing society, healthy ageing has become a key challenge. Engagement in physical activity, and particularly walking, is a key strategy that contributes to healthy ageing amongst older adults. The purpose of the present study was to evaluate the efficacy of a group walking program for older adults that incorporates the 5R Shared Leadership Program (5RS). By implementing a structure of shared leadership and strengthening peer leaders’ identity leadership, 5RS aims to cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…The finding of no direct relationship between walking and age or gender is consistent with prior research and indicates that walking is a viable PA tool for both men and women, as well as young and old. 30,47,48 Thus, walking is a promising intervention to promote PA for all Korean adults regardless of age or gender groups. In particular, walking requires no special skills and is a good way to achieve aerobic PA guidelines for all age groups with little risk of injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The finding of no direct relationship between walking and age or gender is consistent with prior research and indicates that walking is a viable PA tool for both men and women, as well as young and old. 30,47,48 Thus, walking is a promising intervention to promote PA for all Korean adults regardless of age or gender groups. In particular, walking requires no special skills and is a good way to achieve aerobic PA guidelines for all age groups with little risk of injury.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, walking requires no special skills and is a good way to achieve aerobic PA guidelines for all age groups with little risk of injury. 30,47,48 In a study report with nationally representative data of general population, walking was negatively associated with risk of cardiovascular disease. 48 These authors reported that walking was well accepted by participants without causing adverse events (eg, falls, injuries) and could increase moderate-to vigorous-intensity PA among midlife and older adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Haslam et al, 2017)can have several benefits. For example, tests of the 5R program in sport, exercise, and organizational contexts have demonstrated benefits including increases in group members' team identification, number of practice hours, intrinsic motivation, and commitment to team goals (Fransen, Haslam, et al, 2020;Fransen et al, 2022;Mertens et al, 2020;Slater & Barker, 2019). Of particular interest is the finding, in two of these studies, that group members spent more hours doing group-relevant tasks (i.e., practicing sports) when their leaders were trained in identity leadership (see Mertens et al, 2020;Slater & Barker, 2019).…”
Section: Identity Leaders Can Facilitate Group Members' Greater Atten...mentioning
confidence: 99%
“…A. Haslam et al, 2017)—can have several benefits. For example, tests of the 5R program in sport, exercise, and organizational contexts have demonstrated benefits including increases in group members’ team identification, number of practice hours, intrinsic motivation, and commitment to team goals (Fransen, Haslam, et al, 2020; Fransen et al, 2022; S. A. Haslam et al, 2017; Mertens et al, 2020; Slater & Barker, 2019).…”
Section: Proposed Pathways Through Which Identity Leadership Can Faci...mentioning
confidence: 99%